Dexmedetomidine postconditioning provides renal protection in patients undergoing laparoscopic partial nephrectomy: A randomized controlled trial - Jiang, Lingling; Zhang, Tao; Zhang, Yang; Yu, Dexin; Zhang, Ye (Frontiers in Pharmacology, 2022)
BACKGROUND: For localized disease, partial nephrectomy of small tumors continues to be the gold-standard treatment. However, temporary clamping is routinely performed during this process to control renal blood flow, which can cause renal ischemic/reperfusion injury. We evaluated whether dexmedetomidine postconditioning (DPOC) can reduce renal ischemic/reperfusion injury for patients receiving laparoscopic partial nephrectomy (LPN). METHODS: This randomized double-blind controlled trial included 77 patients who were scheduled for LPN at our hospital. Patients were randomly allocated to the DPOC or control group. DPOC was performed via intravenous administration of dexmedetomidine at 0.6 μg·kg−1 for 10 min immediately after unclamping the renal artery. In the control group, saline was administered in place of dexmedetomidine under the same protocol. All participants underwent a six-month follow-up. The primary outcome were the values of 99mTc-DTPA-GFR in the affected kidney at one and six months post-LPN RESULTS: The GFR values in the DPOC group (35.65 ± 4.89mL·min−1·1.73m−2) were significantly higher than those the control group (33.10 ± 5.41 mL·min−1·1.73m−2; p = 0.022) at one month after LPN. There was no statistically significant difference in GFR value between the two groups at six months after LPN. CONCLUSIONS: DPOC provides therapeutic benefits to LPN patients, at least on a short-term basis, by alleviating renal ischemic/reperfusion injury.